Influence of Er3+ion concentration on optical and photoluminescence properties of Er3+-doped gadolinium-calcium silica borate glasses - C. R. Kesavulu (2018)
© 2016 Elsevier B.V. The Er3+-doped gadolinium calcium silica borate glasses of composition (55-x) B2O3– 10 SiO2– 25 Gd2O3– 10 CaO – x Er2O3, where x = 0.0, 0.5, 1.0, 1.5, 2.0 and 2.5 mol %, have been prepared by conventional melt quenching technique and are characterized through optical absorption, visible and near-infrared (NIR) emission spectra and decay time measurements. Judd-Ofelt (JO) intensity parameters (Ωλ, λ = 2, 4 and 6) have been derived from the absorption spectrum of 0.5 mol % Er2O3doped glass and in turn are used to calculate radiative properties for the important luminescent levels of Er3+ions. The studied glasses show intense and broad green (550 nm) and red (591 nm) visible emissions under at 379 nm excitation. Upon excitation at 980 nm laser diode, an intense 1.53 μm NIR emission has been observed with the maximum full width at half maximum (FWHM) and its value is found to be 106 nm for 2.5 mol % Er3+-doped gadolinium calcium silica borate glasses. This broad luminescence locates in the region of 1420–1635 nm and covers the S, C and L bands. The decay curves of the4I13/2level exhibit exponential nature for all the concentrations. The lifetime of the4I13/2level has found to be decrease from 1.46 to 1.35 ms with increase of Er3+ion concentration. Hence, these results clearly indicate that present glasses are suitable for efficient short and conventional-length optical amplifiers and tunable lasers.